Persepsi Mahasiswa Terhadap Penggunakan Aplikasi ChatGPT dalam Mendukung Pembelajaran di Era Digital Pada Program Studi Teknologi Pendidikan Semester IV Universitas Muhammadiyah Bone - Safitri, Nur Afni; Cheriani; A. Suharman (Forum Cendekia: Jurnal Ilmiah Multidisipliner, 2024)
This research aims to determine students' perceptions of using the ChatGPT application to support learning in the digital era. The research method used was qualitative, data was collected through interviews with 10 students and 2 lecturers in the educational technology study program. The research results show that the majority of students have a positive perception of using ChatGPT as a learning aid. They appreciate this application's ability to provide fast and accurate answers and help in understanding difficult material. However, some students expressed concerns regarding over-reliance on this technology and the potential for reducing student interaction in the learning process.